Analisis Supraharmonics Distortions (9-150 kHz) dengan Metode Fast Fourier Transformation Pada Sistem Photovoltaic terhadap Perubahan Radiasi Matahari dengan Tipe Beban Kapasitif - Muhammad, Nagib (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Photovoltaic convert light into electricity. It uses an inverter to convert DC to AC electricity. Along with the increasing use of photovoltaic, inverter use has also increased. In fact, inverters can produce supraharmonics distortions( 9-150kHz) which will cause problems with devices connected to the system. Based on these problems, this study is focused on observing the disturbance characteristics of photovoltaic system due to variations in irradiation and capacitive load in the frequency range from 9 - 150 kHz. In this study the Fast Fourier Transformation method is used to convert the voltage obtained in the time domain into the frequency domain. The analysis technique used is to compare the results of the photovoltaic output voltage. It is expected that the output of this observations can be a reference for developing regulations of high frequency harmonic for photovoltaic system that connected to the distribution network and could be useful to the researcher in analyzing, predicting and knowing the effects on the electric power system. Based on observations obtained, in general there are three frequencies of dominant disturbances, namely the range 19-29kHz, 69-79Khz, and 140-149kHz so the expectation is that regulations will be made on the three dominant frequencies.